Take high -pressure harmonic current compensation arrangement of idle regulation - SHU GUANLAN (2015)
The utility model relates to a take high -pressure harmonic current compensation arrangement of idle regulation, include: the main circuit is connected with the electric wire netting, pours into the offset current who is used for compensating load current into to the electric wire netting, drive circuit with main circuit connection, drives the switching element in the main circuit, current detection circuit, NOT AND linear load connects, detects real -time load current, still include: the compensation signal generator for generate compensation signal according to user instructions, electric current tracking control circuit, junction current detection circuitry, drive circuit and compensation signal generator carry out the electric current according to compensation signal and trail respectively, generate corresponding control signal and send for drive circuit. Compared with the prior art, the utility model has the advantages of simple effective, improvement system side electric energy quality.